Photocatalytic degradation of methylene blue by robust visible-light-driven polyvinylidene fluoride membranes incorporating Ag2O@CRA photocatalyst: Kinetics analysis and cost assessment - Adday, Abdelmoneim S.; Al-Jubouri, Sama M.; Al-Batty, Sirhan (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The kinetic study of the visible-light-driven photocatalytic degradation of methylene blue (MB) dye by the Ag₂O@CRA heterojunction photocatalyst and robust polyvinylidene fluoride membranes incorporating Ag₂O@CRA heterojunction photocatalyst (PVDF/Ag₂O@CRA) was investigated. This study involves a comparison of the outcomes of the kinetic study performed based on the experimental data of the oxidative photocatalytic degradation of the MB dye. The zero-order, pseudo-first-order, and modified Freundlich kinetic models were applied to accomplish this study. The results showed that the photocatalytic oxidation of the MB dye by the Ag2O@CRA photocatalyst followed the pseudo-first-order kinetic model, and the apparent rate constant (k1) value was 0.1231 min-1. The photocatalytic oxidation of the MB dye by the modified PVDF membrane with 0.3 wt.% Ag2O@CRA photocatalyst followed the pseudo-first-order kinetic model, and the apparent rate constant (k1) value was 0.0196 min-1. Also, the Langmuir-Hinshelwood model was used to model the MB photocatalytic degradation kinetics by the Ag2O@CRA photocatalyst for 10-40 mg/L inlet MB concentrations. Likewise, the Langmuir-Hinshelwood model was used to model the kinetics of the MB photocatalytic degradation by the PVDF membrane with 0.3 wt.% Ag₂O@CRA photocatalyst for 5-20 mg/L inlet MB concentrations. It was found that the intrinsic photocatalysis reaction rate constant (kr) was 0.8286 mg/L.min for the Ag₂O@CRA heterojunction photocatalyst and 0.209 mg/L.min for the PVDF/Ag₂O@CRA photocatalytic membrane. Also, it was found that the equilibrium adsorption constant (Kad.) was 0.3245 L/mg for the Ag₂O@CRA heterojunction photocatalyst and 0.218 L/mg for the PVDF/Ag₂O@CRA photocatalytic membrane. The manufacturing cost for the Ag₂O@CRA photocatalyst and PVDF/Ag₂O@CRA photocatalytic membrane was estimated to be $2.45/10 g and $78/m², respectively.